Premnaodoroside A and 10-o-trans-p-methoxycinnamoylcatalpol, two iridoid glycoside derivatives from the leaves of Premna integrifolia L - Bich Hang, Nguyen Thi; Ky, Pham Thanh; Minh, Chau Van; Thao, Nguyen Phuong; Kiem, Phan Van (Vietnam Journal of Chemistry, 2014)
From the leaves of Premna integrifolia L. two iridoid glycoside derivatives premnaodoroside A (1) and 10-O-trans-p-methoxycinnamoylcatalpol (2) were isolated. Their chemical structures were elucidated by means of ESI-mass MS, 1H-NMR, 13C-NMR (CPD and DEPT), HSQC, and HMBC spectra in comparison with the literature. This is the first report of 1 and 2 from P. integrifolia species.